Optimization of Process Parameters for Increasing Material Removal Rate for Turning Al6061 Using S/N Ratio. (2016) - Rajendra, B.; Deepak, D.
Abstract: Modern industries strive to improve the quality of their product by choosing proper materials and methods. Selection of materials of high strength to weight ratio like aluminum and setting of optimum machining parameters ensures the desired quality of product at affordable cost. Industries look for high productivity and better surface finish in machining operations which depends on process parameters. In this article the process parameters such as feed rate, cutting speed and depth of cut are selected to optimize the material removal rate in turning of Al-6061. The analysis is carried out using signal to noise ratio for predicting optimum process parameters. The effect of process parameters on material removal is discussed in this article.